Effectiveness of the Application of the Integrated Population Information System (Sintren) in the Issuance of Death Certificates at the Population and Civil Registration Office of Cirebon Regency - Rico Mulyana; Diky Fajri Nurmansyah; Iskandar Zulkarnaen; R. Mahendra Haryo Bharoto (Pusat Publikasi Nusantara, 2024)
The Integrated Population Information System (SINTREN) is a collection of actions to organize and distribute death certificate documents and population data electronically or via the internet using existing technology, communication, and information facilities. The SINTREN system is used with the aim of providing convenience in population administration services related to death certificates in Cirebon Regency. This research aims to review whether the management of the application or website is able to cut the distance and time of users to be more efficient. The research employs a qualitative approach through observation, documentation, and observations, with a particular focus on informants who were directly involved in the application of the SINTEREN application for issuing death certificates. Data analysis was conducted using Budiani's theory of effectiveness, which includes evaluating the accuracy of program goals, the effectiveness of program socialization, the achievement of program objectives, and the monitoring mechanisms in place. The study contributes by analyzing and interpreting data collected from various sources, providing insights into its implementation, functionality, and impact on improving population and civil registration services. This study could help identify areas for improvement, enhance system efficiency, and inform future policy decisions regarding population information management in the region.